Doxycycline versus prednisolone as an initial treatment strategy for bullous pemphigoid: a pragmatic non-inferiority randomised controlled trial - Williams, Hywel C.; Wojnarowska, Fenella; Kirtschig, Gudula; Mason, James; Godec, Thomas R.; Schmidt, Enno; Chalmers, J.R.; Childs, Margaret; Walton, Shernaz; Harman, Karen; Chapman, Anna; Whitham, Diane; et al. (Elsevier, 2017)
Background: Bullous pemphigoid (BP) is a blistering skin disorder with increased mortality. We tested whether a strategy of starting treatment with doxycycline conveys acceptable short-term blister control whilst conferring long-term safety advantages over starting treatment with oral corticosteroids. Methods: Pragmatic multi-centre parallel-group randomised controlled trial of adults with BP (≥3 blisters ≥2 sites and linear basement membrane IgG/C3) plus economic evaluation. Participants were randomised to doxycycline (200 mg/day) or prednisolone (0·5 mg/kg/day). Localised adjuvant potent topical corticosteroids (<30 g/week) was permitted weeks 1-3. The non-inferiority primary effectiveness outcome was the proportion of participants with ≤3 blisters at 6 weeks. We assumed that doxycycline would be 25% less effective than corticosteroids with a 37% acceptable margin of noninferiority. The primary safety outcome was the proportion with severe, life-threatening or fatal treatment-related adverse events by 52 weeks. Analysis used a regression model adjusting for baseline disease severity, age and Karnofsky score, with missing data imputed. Results: 132 patients were randomised to doxycycline and 121 to prednisolone from 54 UK and 7 German dermatology centres. Mean age was 77·7 years and 68.4% had moderate to severe baseline disease. For those starting doxycycline, 83/112 (74·1%) had ≤3 blisters at 6 weeks compared with 92/101 (91·1%) for prednisolone, a difference of 18·6% favouring prednisolone (upper limit of 90% CI, 26·1%, within the predefined 37% margin). Related severe, life-threatening and fatal events at 52 weeks were 18·5% for those starting doxycycline and 36·6% for prednisolone (mITT analysis), an adjusted difference of 19·0% (95% CI, 7·9%, 30·1%, p=0·001). Conclusions: A strategy of starting BP patients on doxycycline is non-inferior to standard treatment with oral prednisolone for short-term blister control and significantly safer long-term.